2020
DOI: 10.7150/ijbs.40923
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of sFRP2 in Cardiac Development and Cardiovascular Disease

Abstract: The Wnt signaling pathway plays important roles in organ development and disease processes. Secreted frizzled-related protein 2 (sFRP2), a vital molecule of Wnt signaling, can regulate cardiac development and cardiovascular disease. Recent studies have suggested that sFRP2 is not only an antagonist of the canonical Wnt signaling pathway, but also has a more complex relationship in myocardial fibrosis, angiogenesis, cardiac hypertrophy and cardiac regeneration. Here, we review the role of sFRP2 and Wnt signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…SFRPs may activate or inactivate Wnt-signaling and therefore, their role in the pathogenesis of AVS is currently unknown and remains controversial in other cardiac pathologies as well (Bovolenta et al, 2008;Foulquier et al, 2018). Of these molecules, SFRP2 is the most widely studied in the context of cardiac development and disease (Foulquier et al, 2018;Wu et al, 2020). For example, in animal models of myocardial infarction, SFRP2 gene deletion attenuated fibrosis and improved cardiac function, while treatment with SFRP2 antibody reduced apoptosis and fibrosis (Kobayashi et al, 2009;Mastri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…SFRPs may activate or inactivate Wnt-signaling and therefore, their role in the pathogenesis of AVS is currently unknown and remains controversial in other cardiac pathologies as well (Bovolenta et al, 2008;Foulquier et al, 2018). Of these molecules, SFRP2 is the most widely studied in the context of cardiac development and disease (Foulquier et al, 2018;Wu et al, 2020). For example, in animal models of myocardial infarction, SFRP2 gene deletion attenuated fibrosis and improved cardiac function, while treatment with SFRP2 antibody reduced apoptosis and fibrosis (Kobayashi et al, 2009;Mastri et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…30 As a vital molecule of the Wnt signaling, sFRP2 can regulate cardiac development and cardiovascular disease. 31 MiRNAs as a class of small noncoding RNAs play a central role in cardiogenesis, heart function, and pathology. 32,33 It has been reported that miR-142 contributes to early cardiomyocyte differentiation of mouse ES cells, 34 miR-335 could regulate human cardiac mesoderm and progenitor cell differentiation, 35 whereas miR-130 acts as a necessary linkage for the negative Fgf8-Bmp2 feed-back as responsible to achieve early cardiac specification.…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis of DEG are closely related to obesity associated type 2 diabetes mellitus genes and advancement. KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%